Nivel de ventas del Comercial D-Fasil ubicado en el Recinto Mata de Cacao, cantón Babahoyo, provincia de Los Ríos periodo 2023. - Murillo Montiel, Melissa Alexandra (2024)
The objective of this study was to: analyze the sales levels of the D-Fasil commercial located in the Mata de Cacao facility, Babahoyo canton, province of Los Ríos, period 2023, of which emphasis is placed on the variable studied: Sales level. To carry out this case study, the user experience method was used to learn about the behaviors, needs, motivations, trends and comments of customers. Therefore, for data collection, an interview with the owner was implemented, which is part of the qualitative information regarding the processes carried out within the business, and a survey for frequent customers where quantitative results were obtained on dissatisfaction in the business. variety of products, customer service by collecting statistical data on the factors that affect it. The use of these two techniques allowed a better understanding where it is concluded that the company does not have a variety of product brands and customers do not feel satisfied with the attention received.